2008
DOI: 10.1002/ptr.2626
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of colitis injury in rats using Garcinia cambogia extract

Abstract: Inflammatory bowel disease (IBD), Crohn's disease and ulcerative colitis are chronic enteropathies that probably result from a dysregulated mucosal immune response. These pathologies are characterized by oxidative and nitrosative stress, leukocyte infiltration and up-regulation of pro-inflammatory substances. Current IBD treatment presents limitations in both efficacy and safety that stimulated the search for new active compounds. Garcinia cambogia extract has attracted interest due to its pharmacological prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…This method recognizes oxidized bases, and this assay has been used to determine oxidative DNA damage, which has been implicated in several health conditions [59]. Few studies have assessed the levels of oxidative tissue damage in experimental models of colitis using the comet assay [38,39,62]. The results of these studies revealed that levels of oxidative DNA damage were related to histological features characteristic of colitis, thereby confirming the validity of this method in assessment of oxidative tissue damage [38].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This method recognizes oxidized bases, and this assay has been used to determine oxidative DNA damage, which has been implicated in several health conditions [59]. Few studies have assessed the levels of oxidative tissue damage in experimental models of colitis using the comet assay [38,39,62]. The results of these studies revealed that levels of oxidative DNA damage were related to histological features characteristic of colitis, thereby confirming the validity of this method in assessment of oxidative tissue damage [38].…”
Section: Discussionmentioning
confidence: 68%
“…3 Levels of DNA damage after ex vivo H 2 O 2 challenge in colon epithelial cells in segments with and without fecal stream, 2 and 4 weeks after daily irrigation with enemas containing saline solution or 5-ASA, respectively. ** P \ 0.01; AU arbitrary units level of individual cells [59][60][61][62][63][64]. It combines the simplicity of biochemical techniques for detecting DNA single-strand breaks (strand breaks and incomplete excision repair sites), alkali-labile sites, and cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…The G. cambogia extract effectively reduced colonic IL-1 β expression and was also effective in inhibiting the iNOS colonic expression induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS). It was found that the administration of the extract caused a substantial reduction in the COX-2 expression, as well as in the upregulation of PGE 2 caused by TNBS in the colon [24]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the fruit extract possesses hypolipidemic properties and anti-adipogenic and appetite-suppressor effects. [116117] A recent finding suggests that the extract blocked TNBS-induced colitis in rats by preventing epithelial damage, decreasing the activity of MPO, decreasing the expression of COX-2 and iNOS, reducing colonic PGE2 and IL-1β levels, and reducing epithelial cell DNA damage. [117]…”
Section: Spices With Anti-ibd Effectsmentioning
confidence: 99%